30th Joint Propulsion Conference and Exhibit 1994
DOI: 10.2514/6.1994-3070
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic/heat transfer analysis of discrete site film-cooled turbine airfoils

Abstract: goal is the use of film-cooling, wherein a layer of relatively The overall objective of this study was to examine cool gas is iqjected near the metal surfaces to provide a the aerodynamics and heat transfer characteristics of dis-buffer layer between the hot gas and the protected sursite film-cooled turbine &rf0&. The ob-faces. As operational temperature lev& rise in modern jective was to attempt to predict the three-dimensional gas turbine engines, accurately controlling turbine coolflow about the C3X turbine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Mangani et al [96] analysed the same geometry and experimental test point tested by Laskowski et al [94] for validating a procedure aimed to transform OpenFOAM Hall et al [97] conducted 2D simulations of the internal/film cooled 1988 C3X vane leading edge film cooling data of Hylton et al [89]. The simulations included the film cooling holes and plena and made use of span-wise periodic boundary conditions to minimize the problem size.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mangani et al [96] analysed the same geometry and experimental test point tested by Laskowski et al [94] for validating a procedure aimed to transform OpenFOAM Hall et al [97] conducted 2D simulations of the internal/film cooled 1988 C3X vane leading edge film cooling data of Hylton et al [89]. The simulations included the film cooling holes and plena and made use of span-wise periodic boundary conditions to minimize the problem size.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hylton et al [28,29] of the NASA Lewis Research Center conducted a series of heat transfer tests to provide a database for testing the prediction capabilities of analytical models [30,31]. Their investigations covered a wide range of operating conditions and geometries under simulated engine conditions.…”
Section: Computational Modelmentioning
confidence: 99%
“…In a pure streamwise injection case, a symmetric vortex system is established. In a numerical investigation of a showerhead cooling configuration by Hall, Topp and Delaney (1994), it was observed that effects caused by these vortex systems could lead to a cooling flow effectiveness degradation and lift-off of the cooling jet. Besides the negative impact on the cooling performance, the mixing out of the vortices with the main flow generates further aerodynamic losses.…”
Section: Cooling Air Injection Phenomenamentioning
confidence: 99%